Identity Transformation in Cruella Movie: Psychosocial Development Perspective - Rahmasari, Vetty Alfi; Nugroho, Abdillah (FKIP - Universitas Tanjungpura, 2025)
The present study is anchored in the notion that the formation of human identity is inextricably linked to social interaction and the impact of trauma. The film Cruella (2021) has been selected as a case study, as it exemplifies the intricate transformation of the protagonist's identity (Estella to Cruella) through the medium of fashion, expression, and psychosocial dynamics. The objective of the present research is twofold: firstly, to analyse the factors that trigger identity transformation, and secondly, to describe the process of change in the film. The methodological approach adopted is qualitative, incorporating document analysis techniques (e.g., film observation, dialogue transcription, and key scene screenshots). These techniques are then analysed through dialogue segmentation, interpretation of transformation themes, and contextualisation of Erikson's psychosocial development theory. The results of the study indicate the following: (1) The factors that precipitate transformation include the trauma of the mother's death and the Baroness' betrayal as external catalysts, as well as the repression of the dark side (shadow) as an internal driver; (2) The process of change is visualised in three phases: persona formation (the good and obedient false identity of